2022
DOI: 10.1093/ofid/ofac492.192
|View full text |Cite|
|
Sign up to set email alerts
|

114. Long-term Protection Against Herpes Zoster (HZ) by the Adjuvanted Recombinant Zoster Vaccine (RZV): Interim Efficacy, Immuno and Safety Results at Approximately 10 Years after Initial Vaccination

Abstract: Background For the first time, we present data describing vaccine efficacy (VE), immunogenicity persistence and safety up to approximately 10 years after primary vaccination against HZ with RZV. We have previously shown that RZV demonstrated high VE against HZ in adults ≥ 50 years of age (YOA) participating in 2 phase 3 clinical trials (ZOE-50, NCT01165177 and ZOE-70, NCT01165229), and VE persisted up to year (Y) 2 in the interim analysis of the extension study (ZOSTER-049, NCT02723773). Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
0
9
0
2
Order By: Relevance
“…It is very likely that dialysis patients benefit from the previous contact with VZV and thus from a pre-existing immune response that was boosted by the two HZ/su vaccine doses. In a study with healthy individuals, robust immunogenicity of HZ/su has already been shown to persist over a period of 10 years 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very likely that dialysis patients benefit from the previous contact with VZV and thus from a pre-existing immune response that was boosted by the two HZ/su vaccine doses. In a study with healthy individuals, robust immunogenicity of HZ/su has already been shown to persist over a period of 10 years 57 .…”
Section: Discussionmentioning
confidence: 99%
“…It is very likely that dialysis patients benefit from the previous contact with VZV and thus from a pre-existing immune response that was boosted by the two HZ/su vaccine doses. In a study with healthy individuals, robust immunogenicity of HZ/su has already been shown to persist over a period of 10 years 57 . Similar long-term follow-up data are not yet available for immunocompromised individuals but are important in light of our findings that cellular and humoral immunity appears less stable in dialysis patients than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Inzwischen liegen Daten aus insgesamt 10 Jahren vor, mit einer Gesamtwirksamkeit von 89 %, siehe Abb. 2 21 . Dabei konnte die langfristige Persistenz der humoralen und zellulären Immunantwort gezeigt werden 21 , 22 .…”
Section: Herpes Zosterunclassified
“…2 21 . Dabei konnte die langfristige Persistenz der humoralen und zellulären Immunantwort gezeigt werden 21 , 22 . Bis zum ersten Quartal 2022 nahmen nur 11,5 % der Berechtigten ab 60 Jahren die Vakzinierung in Anspruch, die zweite Impfung sogar nur 7,7 % 23 .…”
Section: Herpes Zosterunclassified
“…RZV vaccination has an acceptable safety pro le (27) and leads to high and sustained e cacy against HZ (> 84%), including in people aged 70 years and above) (28-30), and is expected to be at least cost effective (31) and potentially cost-saving (32) in aged patients (≥ 50 years) (33,34). It is thought that both the antibody and T-cell response to the vaccine are important to prevent reactivation of VZV and HZ (35).…”
mentioning
confidence: 99%